First report of the presence of small hive beetle, Aethina tumida, in africanized honey bee colonies in Nicaragua. Technical Note. - Calderón Fallas, Rafael A. (2015)
The small hive beetle (SHB), Aethina tumida, is a pest in honey bee colonies that has spread south across the American continent. However, to date there are few reports of the presence of this beetle in Central American countries. This paper confirms that the beetles analyzed at the Bee Pathology lab of the Tropical Beekeeping Research Center coming from honeybee colonies in San Juan del Sur-Rivas correspond to the small hive beetle, Aethina tumida, which constitutes the first official report of this pest in africanized honey bee colonies in Nicaragua.